Intercultural understanding in global education communities : tracing intercultural education in a pre-service teacher training program at the University of Stellenbosch - Noble, Nicole C. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Education)--University of Stellenbosch, 2005.